The Effect of Virtual Learning on Medical Student Professionalism: A Systematic Literature Review - Syarifah, Mustika Chasanatusy; Akbar, Dimas Arendra Aidilfi (Jurnal Medis Islam Internasional, 2022)
Background: Education is an action to develop a potential of human resources accompanied by learning facilities. Education itself has long been attached and developed in human life until now. The number of Covid-19 transmissions in Indonesia is increasing and causing many victims. To break the chain of spreading this virus, the government has formulated a policy that requires students throughout Indonesia to study from home. So that the learning process is free from these conditions, alternative steps are taken, namely through virtual learning. Objective : The purpose of this study is to compare the literature that has subject matter related to evaluating journals according to the PRISMA and PICO (Problem, Intervention, Comparison, Outcome) methods. Some data were taken from ten articles that were included in the inclusion criteria, including year, keywords, research title, population. Methods: This systematic literature review is based on an analysis of the literature available in the Pubmed, Elsevier, and Google Scholar databases in English. Results: From the 10 literatures that have been analyzed, 8 of them state that virtual learning is considered to have the potential to create professional values ​​for medical students Conclusion: The COVID-19 pandemic has certainly had an impact on learning activities and could affect the professionalism of medical students, but this can be overcome if the campus is able to provide adequate facilities.